Mill girls and strangers : single women's independent migration in England, Scotland, and the United States, 1850-1881 - Gordon, Wendy M., 1967- (State University of New York Press, 2002)
"In the nineteenth-century mill towns of Preston, England; Lowell, Massachusetts; and Paisley, Scotland, there were specific demands for migrant and female labor, and potential employers provided the necessary respectable conditions in order to attract them. Using individual accounts, this innovative and comparative study examines the migrants' lives by addressing their reasons for migration, their relationship to their families, the roles they played in the cities to which they moved, and the dangers they met as a result of their youth, gender, separation from family. Gordon details both the similarities and differences in the women's migration experiences, and somewhat surprisingly concludes that they became financially independent, rather than primarily contributors to a family economy."--Jacket